Mapping the Potential and Quality of Limestone Rocks Using Remote Sensing Method (Study Case: Semanding, Sub District Tuban) - Bangun Muljo Sukojo; Rizki Ramdhani (Institut Teknologi Sepuluh Nopember, 2019)
The mine Exploration is an activity to find the points where an area could be mined and the area is still mined, for economic value. One of the most important in the work of mining is the calculation of the estimated potential of mine. Estimation of the potential mine played an important role in determining the amount of work the quality, production, how the mining is done, even to estimate the time required to do the mining. With the advancement of technology in the field of remote sensing, computation of the vast potential of the estimation and the quality of limestone can be done using high resolution satellite image data one is Quickbird. Satellite image data can be used for a wide range of research, such as the mapping of rock quality in relation to the exploration of natural resources. Vast potential of Cretaceous rocks in Semanding sub district is dominated by the high potential of an area of 5480,479 ha. To a limestone rock quality obtained based on limestone CaCO3 levels, the most highs quality i.e. have levels of CaCO3 amounted to 6.81%.